2013
DOI: 10.1136/annrheumdis-2013-204185
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, adalimumab levels and clinical response in ankylosing spondylitis patients during 24 weeks of follow-up

Abstract: Adalimumab levels are related to clinical response in AS patients measured with ASDAS and are influenced by ADAb detectable with an ABT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 30 publications
4
45
0
8
Order By: Relevance
“…60,61 This response can occur even when patients are treated with fully human mAbs. [62][63][64] Anti-drug antibodies to the 5 anti-TNF agents approved to treat RA patients have been measured. In the case of adalimumab, a fully human antibody, immunogenicity has been linked with a lack of clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 This response can occur even when patients are treated with fully human mAbs. [62][63][64] Anti-drug antibodies to the 5 anti-TNF agents approved to treat RA patients have been measured. In the case of adalimumab, a fully human antibody, immunogenicity has been linked with a lack of clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-drug Ab are generally reported as detected in up to one third of RA and about 25% of SpA patients [2,[30][31][32][33]. Chimericdrugs (mouse-human), such as IFX, have a greater likelihood of inducing anti-drug Abs production compared to fully human antibodies [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In a third of cases such drugs are ineffective and this is due to primary treatment failure (drug inefficacy or serious side effects) or secondary treatment failure (drug loss of efficacy after initial good response). It has been shown that serum levels of ADA, ETN and IFX correlate with the clinical response in RA, while in ankylosing spondylitis (AS) data are controversial [1][2][3][4]. Similarly, anti-drug Ab levels inversely correlate with drugs levels and therapeutic response [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Одновре-менное назначение иммуносупрессантов снижает имму-ногенность ингибиторов ФНОα [4][5][6][7]. Однако при АС синтетические иммуносупрессоры неэффективны, и вли-яние приема метотрексата (МТ) на эффект ИНФ не дока-зано [8]. При АС выработка АТ к ИНФ ассоциируется со снижением его концентрации в сыворотке крови, потерей эффекта терапии и более высоким риском развития инфу-зионных реакций.…”
Section: Investigation Of a Role Of The Immunogenicity Of Infliximab unclassified
“…Однако в настоящее время нет стандартизированного подхода к определению уровня препарата в сыворотке крови и мониторингу нейтрализую-щих АТ, что существенно затрудняет их оценку и может приводить к ошибочным результатам [25]. При изучении результатов терапии АДА у больных АС было выявлено, что клинический эффект зависит от концентрации препа-рата и формирования АТ к нему, что требует проведения соответствующего мониторинга с целью оптимизации ле-чения [8]. F.B.…”
Section: таблицаunclassified